Climate Change Impacts on Irrigation Requirements of Preserved Forage for Horses under Mediterranean Conditions - Daniela Soares; João Rolim; Maria João Fradinho; Teresa Afonso do Paço (Agronomy, 2020)
Pasture and forage production occupies a large part of the utilized agricultural area in Portugal, a country prone to the effects of climate change. This study aims at evaluating the impacts of climate change on forage irrigation requirements and at defining and assessing different adaptation measures. A second objective focuses on evaluating the impacts on water deficit of rainfed forages. This study was performed in a Lusitano horse stud farm located in Azambuja Municipality, Portugal. The climate change impacts on the crop irrigation requirements and crop water deficit were simulated using the soil water balance model, ISAREG. The reference period considered was 1971–2000 and the climate scenarios were the Representative Concentration Pathways (RCPs) 4.5 and 8.5 (2071–2100). The results show that the adaptation measure aiming at maximum production (several cuts) will increase the irrigation requirements in the different climate change scenarios between 38.4% and 67.1%. The adaptation measure aiming at reducing the water consumption (only one cut) will lead to a reduction in irrigation requirements in the different climate change scenarios, ranging between −31.1% and −64.0%. In rainfed conditions, the water deficit is substantially aggravated in the climate change scenarios.